2023
DOI: 10.1021/acsnano.2c09025
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Materials for Photothermal Carbon Dioxide Hydrogenation: Regulating Solar Utilization and Catalytic Performance

Abstract: Converting carbon dioxide (CO2) into value-added fuels or chemicals through photothermal catalytic CO2 hydrogenation is a promising approach to alleviate the energy shortage and global warming. Understanding the nanostructured material strategies in the photothermal catalytic CO2 hydrogenation process is vital for designing photothermal devices and catalysts and maximizing the photothermal CO2 hydrogenation performance. In this Perspective, we first describe several essential nanomaterial design concepts to en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 103 publications
(30 citation statements)
references
References 105 publications
0
30
0
Order By: Relevance
“…In addition, the excellent photothermal effect of catalysts could promote the kinetics of chemical reactions . Therefore, we assessed the phototo-thermal conversion properties of the studied catalysts (Figure g).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the excellent photothermal effect of catalysts could promote the kinetics of chemical reactions . Therefore, we assessed the phototo-thermal conversion properties of the studied catalysts (Figure g).…”
Section: Resultsmentioning
confidence: 99%
“…44 In addition, the excellent photothermal effect of catalysts could promote the kinetics of chemical reactions. 45 Therefore, we assessed the phototo-thermal conversion properties of the studied catalysts (Figure 3g). It is evident that MnCo 2 O 4 and Ru/MnCo 2 O 4 -2 exhibited a significant increase in surface temperature with irradiation time compared to Ru/Al 2 O 3 and Ru/TiO 2 , indicating that MnCo 2 O 4 could efficiently capture and convert light energy into heat to function as a "heating substrate".…”
Section: Acs Nanomentioning
confidence: 99%
“…Introducing light energy into the conventional thermocatalysis has emerged as a promising strategy to achieve a more rapid conversion by activating reactants with photoinduced charge carriers. More encouragingly, a few recent advances exemplified that light irradiation can influence the configuration of catalytic active sites, rendering a dynamic evolution of the catalyst to tune the overall performance. , Basically, restructuring of the catalyst surface in response to the reaction environment, such as structural and/or compositional evolution, is of paramount importance as it not only determines the structure-performance relationship but also governs the underlying mechanisms over genuine active sites. Linic and co-authors revealed a visible-light-induced photoswitching of the Cu valence state, in which the localized surface plasmon resonance (LSPR) of the metallic Cu core reduced the oxide shell formed in situ on Cu, favoring the selective propylene epoxidation . This strong light-matter interaction is achieved using Cu nanoparticles (NPs) with an adequate diameter (∼40 nm), together with a critical threshold irradiance to maximize the exploitation of LSPR energy.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, very effective strategy of light-driven photothermocatalytic CO 2 reduction using H 2 , [18][19][20][21][22][23][24] H 2 O, [2,[25][26][27][28][29] and CH 4 [30][31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48] as reductants has been developed. It well combines the benefits of photocatalysis (low energy consumption) and thermocatalysis (high catalytic activity).…”
Section: Introductionmentioning
confidence: 99%